Physiological Responses during Competitive Sports Aerobics Exercise (Baltic Journal of Sport and Health Sciences, 2018)
The aim of this study was to characterize heart rate (HR), oxygen uptake and pulmonary ventilation during competitiveaerobic gymnastics routine in a group of elite women athletes. The subjects were Lithuanian aerobic women gymnasts,members of national team (21.6, 4.4) years old). All subjects performed a maximal incremental treadmill test in thelaboratory and competitive aerobic gymnastics exercises in group category. Heart rate was continuously recordedusing the heart rate measurement equipment Polar ACCUREX-Plus. During the incremental treadmill test HRdeflection point and other parameters of aerobic capacity were determined from the relationship of HR to runningspeed. During the aerobic gymnastics routine pulmonary gas exchange parameters and heart rate were continuouslymeasured using the telemetric equipment Cortex 3B. The changes of HR, minute ventilation and oxygen uptake wereanalyzed by adopting monoexponential function.The results showed that HR values during the competitive aerobic gymnastics routine were higher than HR break pointwhich is near the lactate accumulation threshold (reaching 95.2 (4.2)% of maximal HR). Oxygen uptake duringcompetitive routine reached 81.3 (5.8)% of maximal oxygen uptake. Rather high blood lactate accumulation(7.50 mmol / l) at the third minute after exercise show the high intensity of exercise. These results allows us to considerthat aerobic gymnastics is a sport with high cardiorespiratory and metabolic demands, in which aerobic and anaerobicsources are intensely activated.Keywords: aerobic gymnastics, aerobic capacity, pulmonary gas exchange, lactate, heart rate deflection point.